Christoph Valentien : Kunst Machen : 26 Maler und Bildhauer beim Kunst-Machen beobachtet von Christoph Valentien. - Forstbauer, Nikolai B.; Valentien, Christoph (Stuttgart: edition cantz, 1987)
Valentien, Christoph ; Baumgartl, Mortiz ; Beck, Gerlinde ; Bernhard, Franz ; Bramke, Ertmut ; Brodwolf, Jürgen ; Bier, Gerda ; Bier, Wolfgang ; Dreyer, Paul Uwe ; Freimann, Christoph ; Gerken-Grieshaber, Helga ; Goertz, Jürgen ; Hahn, Friedemann ; Hartlieb, Ingrid ; Hauser, Erich ; Jacobi, Peter ; Jacobi, Ritzi ; Fischer, Klaus Jürgen ; Lenk, Thomas ; Müller, Reinhold ; Reuter, Hans Peter ; Schoofs, Rudolf ; Schreiner, Hans ; Sequenc, Frans ; Stoll, Artur ; Vogt, Peter ; Willikens, Ben
biografie
Duits
boek